DESCRIPTION OF THE KNOWLEDGE AND ATTITUDE OF THE OK ROOM NURSE IN GIVING EARLY BREASTFEEDING INITIATION (IMD) AT TIARA HOSPITAL PEMATANG SIANTAR CITY - Ismi Noer Fadilah; Hendri Kurniawan (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
If necessary, a special officer is appointed who is directly responsible for the implementation of IMD administration to newborns. It is hoped that in the teaching and learning process both in the classroom and in the laboratory the administration of IMD can be mastered by every student. This research can be used as evidence based in conducting research with the same variables or with several variables related to the provision of Early Breastfeeding Initiation (IMD).